PENGUKURAN MAGNETORESISTANCE PADA POLIETHYLEN GLICOL (PEG)-COATED NANOPARTIKEL MAGNETITE (Fe3O4) DAN BIOMOLEKUL DENGAN SENSOR THIN FILM GIANTMAGNETORESISTANCE (GMR) - , Alfrie Musa Rampengan, Dr. Edi Suharyadi, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The measurements of magnetoresistance (MR) on polyethylene glycol (PEG)- coated magnetite (Fe3O4) nanoparticles and formalin biomolecules using Giant Magnetoresistance (GMR) thin film sensor with a spin-valve structure of Co90Fe19B4/Cu/Co90Fe19/Mn80Ir20 were carried out by the System Four Point Probe Method (SFPPM). The properties of resultant GMR were strongly affected by the thickness of thin films and the responses of magnetic spins. The measurements of MR at a range of external range were approximately (0-75) gauss. For the thicknesses of 10 nm CoFeB free layer and 2.8 nm Cu barrier, it is found that changes in resistance were (17.0 to 12.0) Î©, while for those of 7 nm CoFeB free layer and of 2.2 nm Cu barrier, the changes in resistance were (37.0- 31.0) Î©. Difference in range of the two GMR structures was caused by difference in thickness of CoFeB free layer and Cu barrier. When it was coated by the magnetite materials of Fe3O4 nanoparticles, those modified by PEG-4000 polymer, and those modified by PEG-4000 polymer that was bonded with formalin biomolecule, change in GMR properties occurred, which was indicated by change in resistance value. It shows that GMR as the magnetite sensor was able to detect behavior of the magnetic spins of Fe3O4 nanoparticles.